PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI TERHADAP KINERJA GURU DI SMP NEGERI 3 PEMATANG SIANTAR TAHUN AJARAN 2022/2023 - Saulus Naolo Nainggolan; Susy A. Sibagariang; Benjamin Albert Simamora (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The results of this research state that: 1) there is a significant influence between the principal's leadership on teacher performance at SMP Negeri 3 Pematangsiantar for the 2022/2023 academic year. With the results obtained, the significant value is 0.002 <0.05. 2) there is a significant influence between teacher work motivation on teacher performance at SMP Negeri 3 Pematangsiantar for the 2022/2023 academic year. With the results obtained, the significant value is 0.000 <0.05. 3) Based on the results of the F test, it is known that the significance value for the influence of X_1 and teacher work on teacher performance so that the third hypothesis Ha is accepted while H0 is rejected. 4) it can be seen that the R Square value is 0.395. So it can be concluded that the principal's leadership and teacher work motivation have a simultaneous or joint effect on teacher performance by 3.95%. And there are still other variables that influence teacher performance.